Pemanfaatan ovitrap dalam pengukuran populasi Aedes sp. dan penentuan kondisi rumah - Lisa Hidayati; Upik Kesumawati Hadi; Susi Soviana (Jurnal Entomologi Indonesia, 2017)
The incidence of dengue hemorrhagic fever (DHF) is still a public health problem in Indonesia. Observations over a period of 20 to 25 years since the beginning of  the discovering of the disease, has show the increase of the diseases incidence every five years. The purpose of this study are 1) study the diversity of Aedes’s mosquitoes in Sukabumi City, 2) measure the Aedes population based on the number of eggs and ovitrap index, and 3) to know the correlation between ovitrap index and house condition. Aedes eggs were collected from 14 villages in Sukabumi City that has the highest incidence rate, started from May 2015 until August 2015. Collecting eggs is done by setting a trap eggs (ovitrap) as many as 230 pieces in 115 homes (indoor and outdoor). The results showed that Ae. aegypti were found inside houses and Ae. albopictus were outside houses. The number of eggs collected from ovitrap inside the houses were three times more than those collected from outside. Ovitrap index inside houses was 60%, or 1.6 times more than the ovitrap index outside the houses (37%) in 14 villages in Sukabumi. Houses with poor ventilation and sanitation increased the risk 3.09 times of number of ovitrap index. The results of this study could be use as basic information for the communities to improved environment hygiene through reduced mosquito breeding sites, thus degraded the incidence of dengue